2010
DOI: 10.1016/j.ejpain.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to heat pain after sad mood induction in female patients with major depression

Abstract: Patients suffering from major depressive disorder (MDD) have been shown to exhibit increased thresholds towards experimentally induced thermal pain applied to the skin. In contrast, the induction of sad mood can increase pain perception in healthy controls. Here, we aimed to test the hypothesis that heat pain thresholds are further increased after sad mood induction in depressed patients. Thermal pain thresholds were obtained from 25 female depressed patients and 25 controls before and after sad mood induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
(40 reference statements)
2
22
0
6
Order By: Relevance
“…Clinical and preclinical studies have demonstrated that altered sensitivity to noxious stimuli, or increased incidence and severity of chronic pain, is associated with a large number of disorders of the central nervous system, including depression Dworkin et al, 1995;Klauenberg et al, 2008;Shi et al, 2010a;Shi et al, 2010b;Terhaar et al, 2010), anxiety disorders (Asmundson and Katz, 2009;Finn et al, 2006;Geuze et al, 2007;Ploghaus et al, 2001;Rivat et al, 2010), multiple sclerosis (Kenner et al, 2007;Olechowski et al, 2009;Solaro et al, 2003) and others. Thus, a passive-avoidance paradigm using air-puff in place of noxious foot-shock may also be preferable for assessment of aversive learning and memory in rodent models of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and preclinical studies have demonstrated that altered sensitivity to noxious stimuli, or increased incidence and severity of chronic pain, is associated with a large number of disorders of the central nervous system, including depression Dworkin et al, 1995;Klauenberg et al, 2008;Shi et al, 2010a;Shi et al, 2010b;Terhaar et al, 2010), anxiety disorders (Asmundson and Katz, 2009;Finn et al, 2006;Geuze et al, 2007;Ploghaus et al, 2001;Rivat et al, 2010), multiple sclerosis (Kenner et al, 2007;Olechowski et al, 2009;Solaro et al, 2003) and others. Thus, a passive-avoidance paradigm using air-puff in place of noxious foot-shock may also be preferable for assessment of aversive learning and memory in rodent models of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Ces seuils étaient diminués dans trois études [4,36,45] et quatre études ont échoué à trouver des différences entre les groupes [19,26,43,47].…”
Section: Seuils De Douleurunclassified
“…Indépendamment de la mesure de la douleur (seuil de douleur, tolérance à la douleur, douleur subjective, mais pas les seuils de sensation), des signes d'hypoalgésie dans la DM, par rapport aux sujets sains, ont été décrits dans sept études utilisant des stimuli thermiques [3][4][5]13,27,31,42], trois études ont rapporté des signes d'hyperalgésie [19,36,45], alors que cinq études ont échoué à démontrer des différences intergroupes sur certaines réponses [17,26,36,43,47].…”
Section: Stimulation Thermiqueunclassified
See 2 more Smart Citations